DETERMINATION OF CHARACTERISTIC VALUES IN NBR 7190/1997 FOR DESIGN AND FIRE SAFETY IN WOOD MATERIALS: HITS AND MISSES - Matos, Carlos [UNESP]; Gomes, JFS; Meguid, S. A. (Inegi-feup, 2015)
Annex B of the Brazilian standard for timber frame projects (NBR 7190: 1997) have normative status and determines that the characteristic values of wood properties must be estimated by an expression that produces conservative estimates. In most situations, this strategy is suitable for design and fire safety in wooden materials due to the high variability of these materials. Unfortunately, the use of this criterion penalizes materials where great efforts were made to achieve a high level of quality control.
Keywords: Fire safety; wood materials